Re-examining the Organization of Healthcare: Institutional, Technological and Clinical Challenges - (:unkn) unknown (European Group for Organizational Studies (EGOS), 2015)
This paper addresses one of the research questions posed by the stream chairs: How do macrolevel (health system), meso-level (organization) and micro-level (individual) changes dynamically interact and translate their effect on performance?